Nuclear Receptor RORα/γ: Exciting Modulators in Metabolic Syndrome and Related Disorders - Gu, Haotian; Hu, Ping; Zhao, Yahui; Liu, Yaya; Wang, Yi-Ting; Ahmed, Abdelkareem A.; Liu, Hao-Yu; Cai, Demin (Frontiers in Nutrition, 2022)
Under the influences of modern lifestyle, metabolic syndromes (MetS) including insulin resistance, obesity, and fatty liver featuring a worldwide chronic disease greatly raises the risk of type 2 diabetes, heart disease, and stroke. However, its pathogenesis is still unclear, and there are limited drugs with strong clinical efficacy and specificity. Given the close connection between impaired lipid metabolism and MetS onset, modulating the lipid metabolic genes may provide potential prospects in the development of MetS therapeutics. Nuclear receptors are such druggable transcription factors that translate physiological signals into gene regulation via DNA binding upon ligand activation. Recent studies reveal vital functions of the NRs retinoic acid receptor-related orphan receptors (RORs) including RORα and RORγ in the genes regulation in lipid metabolism and MetS. This review focuses on the latest developments in their actions on MetS and related metabolic disorders, which would benefit future clinical therapeutic applications.